2020
DOI: 10.3390/ijms21020503
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Intervention Using Fecal Microbiota Combined with Probiotics Promotes Gut Microbiota Maturation, Regulates Immune System Development, and Alleviates Weaning Stress in Piglets

Abstract: Previous studies have suggested that immune system development and weaning stress are closely related to the maturation of gut microbiota. The early-life period is a "window of opportunity" for microbial colonization, which potentially has a critical impact on the development of the immune system. Fecal microbiota transplantation (FMT) and probiotics are often used to regulate gut microbial colonization. This study aims to test whether early intervention with FMT using fecal microbiota from gestation sows comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 79 publications
1
51
0
1
Order By: Relevance
“…Similar to previous works ( Cheng et al, 2018 ; McCormack et al, 2018 ; Brunse et al, 2019 ; Xiang et al, 2020 ), our present study demonstrated that microbiota transplantation following birth significantly promoted the growth of the piglets and improved their intestinal structure, as well as their immune and digestive functions. These beneficial effects in these young pigs are absolutely inseparable from the changes in their gut microorganisms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous works ( Cheng et al, 2018 ; McCormack et al, 2018 ; Brunse et al, 2019 ; Xiang et al, 2020 ), our present study demonstrated that microbiota transplantation following birth significantly promoted the growth of the piglets and improved their intestinal structure, as well as their immune and digestive functions. These beneficial effects in these young pigs are absolutely inseparable from the changes in their gut microorganisms.…”
Section: Discussionsupporting
confidence: 91%
“…Fecal microbe transplantation is mainly used for the treatment of severe diarrhea and enteritis in the clinic ( Cui et al, 2015 ; Haber et al, 2019 ). In recent years, some microbial transplantation studies have been carried out in pigs and other domestic animals ( Cheng et al, 2018 ; Geng et al, 2018 ; McCormack et al, 2018 ; Brunse et al, 2019 ; Xiang et al, 2020 ). The parallel results obtained from these research studies have indicated that early interventions based on microbe transplantation improve the intestinal health of young animals, thereby promoting their growth.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal microbiota transplantation (FMT) is a technique for transplanting the fecal microbiota from a healthy individual into the gut of a recipient individual ( Youngster et al, 2014 ; Lin et al, 2018 ). As an important therapy for intestinal diseases, including inflammatory bowel disease and irritable bowel syndrome ( Borody and Khoruts, 2011 ; Pigneur and Sokol, 2016 ; Heath et al, 2018 ), FMT has attracted some researchers’ attention due to its ability to restore the intestinal microbiota ( Cheng et al, 2018 ; Hu et al, 2018 ; Xiang et al, 2020 ). Over the past decade, FMT has been developed rapidly from initial methods that proposed the use of fresh stool to the use of purified and cryopreserved standardized preparations of fecal microbiota from highly selected donors ( Staley et al, 2017 ; Reygner et al, 2020 ; Tang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding major changes in nasal microbial composition after weaning, we found the same Bacteroides and Prevotella inverse apparent association observed in the faeces. Remarkably, several genera associated to health (such as Lachnospira and Blautia from Lachnospiraceae, and Faecalibacterium and Ruminococcus from Ruminococcaceae) relatively increased, probably promoting the immune and anti-stress functions 29 , while Bergeyella and Fusobacterium, which have been associated to disease [30][31][32] , showed to relatively decrease over time.…”
Section: Discussionmentioning
confidence: 99%